Pengaruh Promosi Online dan Brand Image Terhadap Keputusan Pembelian pada Produk UMKM Kopi Kenangan Ruko Ahmad Yani di Bandar Lampung - Tri Lestira Putri Warganegara; Dita Safitri (Jurnal EMT KITA, 2023)
The purpose of this study is to investigate the impact of online advertising on purchase decisions, the impact of brand image on purchase decisions, and the combined impact of online advertising and brand image on purchase decisions. The study should test her two independent variables: online advertising and brand image. The study population consisted of 100 respondents who ingested Kopi Kenangan Ruko Ahmad Yani in Bandar Lampung and was randomly selected using a random sampling method. Data was collected by questionnaire. The research methods used are multiple regression analysis and testing of validity, reliability, classical hypothesis testing, and hypothesis testing. Collected data was processed using SPSS version 25 software. The results showed that online advertising had a positive and significant impact on the decision to purchase Kopi Kenangan Ruko Ahmad Yani in Bandar Lampung. Brand image also has a positive and significant impact on the purchasing decisions of Kopi Kenangan Ruko Ahmad Yani of Bandar Lampung. In addition, online promotions and brands his image have a positive and significant impact on purchase decisions of Bandar his Lampung Kopi Kenangan Ruco Humad his Yani.